2007
DOI: 10.1002/jmv.20792
|View full text |Cite
|
Sign up to set email alerts
|

IRES complexity before IFN‐alpha treatment and evolution of the viral load at the early stage of treatment in peripheral blood mononuclear cells from chronic hepatitis C patients

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 60 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…Predictive folding however, revealed no effect of this mutation on the calculated thermodynamic stability. The role of nucleotide 243 in maintaining IRES structure was reported in HCV genotype 1b [21] and changes at this position were encountered in patients with viral stabilization. In genotype 1b, A243 pairs with U149, which is lacking in 4a, leading to altered pairing and explains the high rate of mutations at this position in our study population regardless of response to IFNα, thus making it more vulnerable to mutational event in genotype 4a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Predictive folding however, revealed no effect of this mutation on the calculated thermodynamic stability. The role of nucleotide 243 in maintaining IRES structure was reported in HCV genotype 1b [21] and changes at this position were encountered in patients with viral stabilization. In genotype 1b, A243 pairs with U149, which is lacking in 4a, leading to altered pairing and explains the high rate of mutations at this position in our study population regardless of response to IFNα, thus making it more vulnerable to mutational event in genotype 4a.…”
Section: Discussionmentioning
confidence: 99%
“…Although genomic variability in HCV IRES was shown as one mechanism for escaping IFNα effects, there has been www.wjgnet.com controversy with regard to the predictive value of pretreatment IRES genomic variations in determining later response to IFNα [20] . Although domain Ⅲ harbors only 22% of the overall IRES mutations in a mixed genotype population [21] , IRES activity seems to depend more on the location of mutant nucleotides which play the most important roles in IRES activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes in nucleotide may have dramatic effect on translation [Van et al, 2004]. Some studies reported that nucleotide changes in IRES region have influence on response to therapy [Th elu et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…While HCV is mainly hepatotropic, cells of the lymphoid system constitute a secondary site of replication and lymphotropic variants often differ from those circulating in blood [7, 12, 13, 20, 21]. Several studies have shown that sequence changes within the 5′UTR affect the stability of secondary RNA structures and that they affect viral translation and replication efficiency; in addition, they are likely to determine viral tropism to particular cell compartments [2, 3, 57, 14, 22].…”
Section: Discussionmentioning
confidence: 99%